An estimate of the energy production potential of agricultural biomass in the ódz Province - Natalia Szubska-Włodarczyk (European Regional Science Association (ERSA), 2015)
The analysis has demonstrated the theoretical energy-production potential of biomass in the areas of fallow and waste land. Moreover, at this stage, the economic potential of bringing the land into cultivation also seems justifiable. However, there is a need to estimate the cost of processing and energy production by power plants and co-generating power plants. It is necessary to analyse the inclusion of tools for supporting production of renewable energy, as well as to plan the location of decentralised units. Production of biomass for energy purposes requires, first of all, retaining balance between the use of agricultural area for food and energy production. Due to the specific nature of rural areas, it is necessary to develop an integrated approach to land management in order to support sustainable development. There is a need to move away from the model of intensive agriculture in the direction of sustainable agriculture. Development of energy-producing agriculture is conditioned by the modernisation and technological progress in order to displace the conventional model. Agriculture is a sector that has a significant impact on the environment and on quality of life of the population. Therefore, it is an area where it is necessary to initiate action for sustainable development. According to the 2009/28/EC Directive, Poland should achieve the level of 15% of energy being obtained from renewable resources in the total consumption in 2020. This goal will not be achieved without focusing activities on the development of dispersed energy production, including the activation of rural areas. The aim of the study is: to estimate energy production potential of fallow soil and fallow land in the ód Province on the basis of selected energy crops, to calculate the minimum price of energy crops. The following analysis verifies the main research hypothesis, i.e., that the ód Province has a theoretical and economical energy-production potential of biomass production in the areas of fallow soil and fallow land. This paper presents a model of uncultivated agricultural land under appropriately selected energy crops. The main goal of this work is to estimate energy production potential of fallow soil and fallow land in the ód Province on the basis of selected energy crops and to calculate the minimum price of energy crops. The Net Present Value (NPV) method was used to calculate the minimum price, and the literature studies to build the model using. The following analysis verifies the main research hypothesis, i.e., that the ód Province has a theoretical and economical energy-production potential of biomass in the areas of fallow soil and fallow land. The hypothesis was verified positively. The study shows that practicing energy willow achieved the lowest price for generation of 1 MWh .
Keywords: Q1; Q4; Q5; 330; biomass; energy crops; the minimum price; energy and climate policy